2013
DOI: 10.5121/ijcnc.2013.5312
|View full text |Cite
|
Sign up to set email alerts
|

Centrality-Based Network Coder Placement for Peer-To-Peer Content Distribution

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In a similar context, Yufei et al [15] use "control nodes" to cache content based on betweenness centrality. Nguyen and Nakazato [16] proposed a betweenness-centralitybased network coder placement for peer-to-peer (P2P) content distribution. However, they do not consider content placement; they use random linear network coding at every coding node to assist content delivery.…”
Section: Related Workmentioning
confidence: 99%
“…In a similar context, Yufei et al [15] use "control nodes" to cache content based on betweenness centrality. Nguyen and Nakazato [16] proposed a betweenness-centralitybased network coder placement for peer-to-peer (P2P) content distribution. However, they do not consider content placement; they use random linear network coding at every coding node to assist content delivery.…”
Section: Related Workmentioning
confidence: 99%
“…In a similar context, Yufei et al [15] use "control nodes" to cache content based on betweeness centrality. Nguyen and Nakazato [16] proposed a betweenness-centrality-based network coder placement for peer-to-peer (P2P) content distribution. However, they do not consider content placement; they use random linear network coding at every coding node to assist content delivery.…”
Section: Related Workmentioning
confidence: 99%
“…The work of Li et al was followed by Ho et al [6] that showed that random linear combinations construct good network codes with high probability. Previous work [7] has powerfully indicated that using network coding in P2P file sharing system can effectively improve system throughput and handle dynamics of nodes in the network, including node arrival and node departure, node and piece selection, link failure, etc., thereby optimizing system performance. Therefore, we use (n, k) erasure code (a kind of network coding) in our file swarming protocol.…”
Section: Introductionmentioning
confidence: 99%